The International Monetary System, 1844-1870: Arbitrage, Efficiency, Liquidity - Stefano Ugolini (Norges Bank, 2010)
This paper analyses the architecture of the international monetary system which preceded the international gold standard (1844-1870). It builds on a newly-created database made up of more than 100,000 weekly observations on exchange rates, interest rates, and bullion prices in the world's six most important financial centers of the time. Market integration, substitutability of money market instruments, choice of the correct monetary standard reference, and currency liquidity are tested; moreover, an historical analysis is run, with special reference to financial crises. Contrary to received wisdom, the results point to a trend towards increasing multipolarism in the international monetary system before 1870.
hdl:11250/2497438
Keywords: E42; F31; N20; 330; international monetary system; financial integration; money markets; bimetallism